Detection of BK virus in urine from renal transplant subjects by mass spectrometry - Konietzny, R.; Fischer, R.; Ternette, N.; Wright, C.; Turney, B.; Chakera, Aron; Hughes, D.; Kessler, B.; Pugh, C. (BioMed Central Ltd., 2012)
Background: The diagnosis and management of BK virus (BKV) reactivation following renal transplantation continues to be a significant clinical problem. Following reactivation of latent virus, impaired cellular immunity enables sustained viral replication to occur in urothelial cells, which potentially leads to the development of BKVassociated nephropathy (BKVAN). Current guidelines recommend regular surveillance for BKV reactivation through the detection of infected urothelial cells in urine (decoy cells) or viral nucleic acid in urine or blood. However, these methods have variable sensitivity and cannot routinely distinguish between different viral subtypes. We therefore asked whether mass spectrometry might be able to overcome these limitations and provide an additional noninvasive technique for the surveillance of BKV and identification of recipients at increased risk of BKVAN. Results: Here we describe a mass spectrometry (MS)-based method for the detection of BKV derived proteins directly isolated from clinical urine samples. Peptides detected by MS derived from Viral Protein 1 (VP1) allowed differentiation between subtypes I and IV. Using this approach, we observed an association between higher decoy cell numbers and the presence of the VP1 subtype Ib-2 in urine samples derived from a cohort of 20 renal transplant recipients, consistent with the hypothesis that certain viral subtypes may be associated with more severe BKVAN. Conclusions: This is the first study to identify BK virus proteins in clinical samples by MS and that this approach makes it possible to distinguish between different viral subtypes. Further studies are required to establish whether this information could lead to stratification of patients at risk of BKVAN, facilitate distinction between BKVAN and acute rejection (AR), and ultimately improve patient treatment and outcomes. © 2012 Konietzny et al.; licensee BioMed Central Ltd.